The Use Of Grammatical and Lexical Cohesion In Short Story “Nyanyian Pilu Meo Oni yang Terdengar dari Hutan” By Lita Lestianti - Herawati, Yuke Elvin; Khoirun Nisa', Dwi Susanti; Pradani, Rizky Fitriyanti; Arifin, Muhammad; Utami, Sri (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
The short story studied in this study is "Nyanyian Pilu Meo Oni Yang Terdengar Dari Hutan" by Lita Lestianti which was written in 2019. The purpose of this study is to describe the use of grammatical and lexical cohesion in short story. This research implemented a qualitative method. Data collection techniques using reading and recording techniques. The data collection procedure includes preparing data sources, reading and listening to the contents of the short story, reducing and marking the data, and recording data. The data analysis method in this study is the distribution method. The data analysis technique is descriptive analysis with data analysis procedures, namely identification, classification, data reduction and conclusions. The results of this study revealed the use of grammatical and lexical cohesion in short story which include grammatical cohesion, namely reference, substitution, omission (ellipsis), and conjunctions and lexical cohesion, namely repetition, synonyms (similarities), antonyms (opposite words), hyponyms (part or content relationships), collocations (word conjunctions), and equivalence.